Computer-model-based audio and its influence on science learning by people who are blind. Issue 5 (18th August 2019) - Lahav, Orly; Hagab, Noha; Levy, Sharona Tal; Talis, Vadim
ABSTRACT: Access to curriculum learning materials is a central need for students who are blind. This research examined the use of Listening-to-Complexity (L2C) based on NetLogo, an agent-based modeling language enabling exploration and construction of models of complex systems. L2C, designed for users who are blind, provides several auditory streams synchronically through sonified feedback. Studied here is a learning curriculum integrating L2C interactions, which covering scientific conceptual knowledge, systems reasoning, and Kinetic Molecular Theory of gas and gas laws in chemistry. The research included ten participants who are blind, using three data collection tools: background questionnaire, pre- and posttest questionnaires, and learning curriculum with the sonified models. Results indicate that the sonified model facilitates access to key challenging scientific concepts, including complex phenomena. Findings indicate gains in learning science content; participants were able to collect and construct scientific knowledge through L2C interactions. There are likely long-term practical benefits in science education for students who are blind, which will facilitate their inclusion in a general K-12 program.